THE EYES OF THE TREE: PERCEIVING, MONITORING, UNDERSTANDING, AND COUNTERING BIOLOGICAL INVASIONS IN TIMES OF RAPID BIOCULTURAL HOMOGENIZATION - Crego, Ramiro D.; Ward, Nora; Jimenez, Jaime E.; Massardo Vega, Cristina Elvira Francisca; Rozzi Marin, Ricardo Roberto (My University, 2018)
The Anthropocene is marked by a pervasive process of biocultural homogenization that includes losses of biological and cultural diversity. The process is evident in the case of some biological invasions. Biocultural ethics aims to counteract this homogenization process. Toward this aim, the Field Environmental Philosophy (FEP) methodological approach has been designed. FEP has been conceived and implemented at the Americas' southernmost site of the International Long-term Ecological Research (ILTER) network, the Omora Ethnobotanical Park, to integrate ecological and philosophical research into biocultural conservation. ILTER sites are intended to investigate and monitor global socio-environmental change. At the same time, ILTER sites aim to contribute reorienting this change toward trajectories of socio-environmental sustainability. However, to achieve these aims the ILTER network presents three major limitations: (i) it is focused on biophysical research, largely ignoring relevant cultural dimensions; (ii) it is focused on theoretical studies, frequently postponing applied studies; (iii) and the distribution of ILTER sites has a marked geographical bias towards the northern hemisphere. The objective of this work is to contribute to overcome these three limitations by integrating ecological, philosophical, and technological components on the basis of the work conducted on an invasive species that has recently arrived to the southern end of the Americas, the American mink (Neovison vison). A main result of this study is the composition of the metaphor "the eyes of the tree." This metaphor integrates research on scientific, philosophical and Native American forms of ecological knowledge and worldviews, and calls for conservation actions in a transdisciplinary way. This metaphor proposes a contextual view to observe, monitor, and understand the problematic of invasive species. It contributes to counteract the impact of exotic species through education and control practices that prioritize the ecosystem as a whole. In this way, it triggers approaches that are complementary to those that privilege of individual welfare over of the integrity of the biotic community.
Keywords: biocultural homogenization; environmental field philosophy; ilter; ltser; invasive species